Community perceptions and attitudes towards the management of protected areas in Seychelles with Morne Seychellois National Park as case study - Daniel Etongo; Heather Lafleur; Terence Vel (World Development Sustainability, 2023)
Designated as a protected area (PA) in 1979, the Morne Seychellois National Park (MSNP) hosts one of the three Ramsar sites in Seychelles – the Mare Aux Cochon (MAC). The park occurs partly in an area with private land ownership suffering from development pressure. Understanding community perceptions and attitudes towards the MSNP can improve the park's role in addressing climate change and biodiversity loss. This study used a stratified random sampling of 130 households to (i) determine socio-demographic factors that influence local communities' attitudes toward biodiversity conservation in the MSNP, (ii) pereceived importance of the MSNP, (iii) to assess what activities are (un)acceptable in the MAC and the rest of the park, and (iv) who has rights to access, land ownership and land-use decision making in the park. The findings indicated that the positive behavior of local communities towards biodiversity conservation is influenced by the frequency of visits and benefits derived in terms of ecosystem services at the 5% significance level. Chief among the importance of the MSNP as viewed by community members included ecotourism (93.5%), biodiversity conservation (84.6%), and environmental protection (66.7%). Respondents generally perceived that low-impact activities should occur at the MAC and the rest of the park. However, the impact from activities such as camping and picnic, hiking, and nature walks, and the harvesting of non-timber forest products, a non-tourism activity, was of greater concern in the MAC. On the other hand, high-impact activities, such as logging and infrastructural development, received over 70% disagreement in the MAC and the rest of the park. Our findings have implications for Seychelles’ land acquisition in the public interest Act 1996, which is silent about land within PAs.